2021
DOI: 10.3389/fneur.2021.706169
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic Neuropathies: What's New Since the 2004 Recommended Diagnostic Criteria

Abstract: The diagnostic criteria published by the PNS (Paraneoplastic Neurological Syndromes) Euronetwork in 2004 provided a useful classification of PNS, including paraneoplastic neuropathies. Subacute sensory neuronopathy (SSN) was the most frequently observed peripheral PNS, whereas other forms of neuropathy, as sensory polyneuropathy, sensorimotor polyneuropathy, demyelinating neuropathies, autonomic neuropathies, and focal nerve or plexus lesions, were less frequent. At the time of publication, the main focus was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 156 publications
(150 reference statements)
0
16
0
3
Order By: Relevance
“…Neurodegeneration is a recognised feature of paraneoplastic disease. It cannot be overemphasised how important the newly described association of increased blood Nf levels in this context might be (Mizenko et al, 2021; Zoccarato et al, 2021). This is because a challenge for neuro‐immunology remains the limited number of validated paraneoplastic antibodies, but frequently a high clinical suspicion of an association remains in individuals who do not harbour any of the known paraneoplastic antibodies.…”
Section: Diseasesmentioning
confidence: 99%
“…Neurodegeneration is a recognised feature of paraneoplastic disease. It cannot be overemphasised how important the newly described association of increased blood Nf levels in this context might be (Mizenko et al, 2021; Zoccarato et al, 2021). This is because a challenge for neuro‐immunology remains the limited number of validated paraneoplastic antibodies, but frequently a high clinical suspicion of an association remains in individuals who do not harbour any of the known paraneoplastic antibodies.…”
Section: Diseasesmentioning
confidence: 99%
“…Subacute sensory neuronopathy is the most common type of peripheral paraneoplastic neurological syndrome [43]. Other syndromes include sensory polyneuropathy, sensorimotor polyneuropathy, demyelinating neuropathy, autonomic neuropathy, focal nerve lesions, and plexus nerve lesions [43]. Paraneoplastic neuropathy is associated with onconeural or intracellular antibodies or neuronal surface antibodies [43].…”
Section: Paraneoplastic or Neoplastic Neuropathymentioning
confidence: 99%
“…Other syndromes include sensory polyneuropathy, sensorimotor polyneuropathy, demyelinating neuropathy, autonomic neuropathy, focal nerve lesions, and plexus nerve lesions [43]. Paraneoplastic neuropathy is associated with onconeural or intracellular antibodies or neuronal surface antibodies [43]. In late-stage cancer, patients may experience sensory-motor neuropathy, a relatively mild condition distinct from CIPN [43].…”
Section: Paraneoplastic or Neoplastic Neuropathymentioning
confidence: 99%
See 1 more Smart Citation
“…Small cohort studies have reported the incidence of paraneoplastic syndromes to be 11%–16% in lung cancer patients ( 2 4 ). Paraneoplastic disorders are diagnoses of exclusion; however, diagnostic criteria have been developed for some syndromes with available specialized testing ( 5 , 6 ). These syndromes occur due to two main mechanisms: the generation of physiologic antibodies directed against a tumor epitope that cross reacts with normal tissue (neurologic paraneoplastic syndromes) and abhorrent production of a functional soluble factor ectopically produced by tumor cells (endocrine paraneoplastic syndromes) ( 7 ).…”
Section: Introductionmentioning
confidence: 99%